Kinetics of Hydrolysis of p-methoxyphenyl Phosphorotriamidate in the pH Region - Singh, V.; Prabha, S. (Asian Journal of Chemistry, 2010)
Hydrolysis of p-methoxyphenyl phosphorotriamidate has been carried out in the pH range 1.24 to 10.0 in 30% acetic acid at 65°C. A higher value of rate coefficients at pH 1.24 is based on the presence of conjugate acid form while the neutral form is active in the entire pH range examined. Three maxima are obtained at pH 4.17, pH 6.43 and pH 10, the first two corresponding to the maxima and minmma observed for the corresponding mono- and di-esters, at which pH both the esters. hydrolyse via their monoanion forms. Both the values are probably the mixed rates and are possibly not analysed by the methods used for this purpose. Arrhenius parameters favour bimolecular route of hydrolysis for the neutral form; solvent effect study carried out at pH 1.61 and 4.17 indicates that the rates are elevated (1.61 pH) nearly two and a half times, which is attributed to the lowering of dielectric constant of acetic acid medium which favours the reactions involving protonation. At pH 4.17, when the solvent in increased by nearly one and a half times, the rates are reduced but when the acetic acid is as high as 90% the rates are found to be doubled. Thus most probably here the solvent helps to stabilise the basic leaving group by some sort of salt formation. Comparative kinetic data of some triesters via their neturai forms has been used to decide the P—N bond cleavage, depending upon the similarity in behaviour in all cases.